Differential binding of colors to objects in memory: red and yellow stick better than blue and green - Kuhbandner, Christof; Spitzer, Bernhard; Lichtenfeld, Stephanie; Pekrun, Reinhard (Frontiers in Psychology, 2015)
Both evolutionary considerations and recent research suggest that the color red serves as a signal indicating an object’s importance. However, until now, there is no evidence that this signaling function of red is also reflected in human memory. To examine the effect of red on memory, we conducted four experiments in which we presented objects colored in four different colors (red, green, blue, and yellow) and measured later memory for the presence of an object and for the color of an object. Across experiments, we varied the type of objects (words versus pictures), task complexity (single objects versus multiple objects in visual scenes), and intentionality of encoding (intentional versus incidental learning). Memory for the presence of an object was not influenced by color. However, in all four experiments, memory for the color of an object depended on type of color and was particularly high for red and yellow-colored objects and particularly low for green-colored objects, indicating that the binding of colors into object memory representations varies as a function of color type. Analyzing the observers’ confidence in their color memories revealed that color not only influenced objective memory performance but also subjective confidence. Subjective confidence judgments differentiated well between correct and incorrect color memories for red-colored objects, but poorly for green-colored objects. Our findings reveal a previously unknown color effect which may be of considerable interest for both basic color research and applied settings like eyewitness testimony in which memory for color features is relevant. Furthermore, our results indicate that feature binding in memory is not a purely automatic process by which any attended feature is automatically bound into a unitary memory representation. Rather, binding in memory seems to vary across different subtypes of features, a finding that supports recent research showing that features of objects are stored in memory.